A Collision Avoidance MAC Protocol with Power Control for Adaptive Clustering Underwater Sensor Networks - Libin Xue; Hong Lei; Rongxin Zhu (Journal of Marine Science and Engineering)
Underwater sensor networks (UWSNs) play a vital role in marine exploration and environmental monitoring. However, due to the characteristics of underwater acoustic channels such as high delay, low bandwidth, and energy limitation, the design of an underwater media access control (MAC) protocol has brought great challenges, and existing MAC protocol designs rarely consider the influence of channel interference factors in networking. Therefore, this paper proposes a collision avoidance MAC protocol for clustering underwater sensor networks. The protocol first classifies users by combining the channel characteristics of underwater nodes and the distance measurement between nodes. Then, based on the clustering network, according to the channel correlation distance measurement between nodes and the communication range of the cluster head (CH), the transmit power in clusters is controlled to reduce the lifetime of the network based on the cumulative reduction in node power consumption. Finally, the cluster structure in each cluster is used to schedule the transmission of member nodes in the cluster, and at the same time, the energy consumption of nodes is reduced while multi-node collision-free transmission is realized. The simulation results show that the throughput of the proposed adaptive power control clustering MAC protocol (APCC-MAC) is 26.5% and 19.5% higher than that of packet-level slot scheduling (PLSS) algorithm and Cluster-Based Spatial–Temporal Scheduling (CSS) algorithm, respectively, providing better communication performance and stability for clustered underwater acoustic networks.